REFUSAL STRATEGIES TO INVITATION BY NATIVE AND NON NATIVE - Wijayanto, Agus (Universitas Muhammadiyah Surakarta, 2013)
In Javanese context, refusal tends to threat the feelings and self worth of addressees while in British, refusal is not normally face threatening or at least it is not as face threatening as it is in the Javanese context. This paper compares sequencing of semantic formulae and adjuncts of refusal to invitations phrased by native speakers of British English and Javanese learners of English. The data of refusal are elicited through written discourse completion tasks (DCT) involving nine scenarios. Refusal strategies are classified based on a modified version of refusal taxonomy by Beebe, Takahashi, and Uliss-Weltz (1990). Overall the refusal strategies employed by the two groups are similar. Few differences in sequencing of semantic fomulae and adjuncts of refusal are due to politeness function.